MO238: Erythroid ACKR1 Expression has a Protective Effect on the Development of Experimental Glomerulonephritis. (3rd May 2022) - Artinger, Katharina; Novitzky-Basso, Igor; Kirsch, Alexander H; Schabhuettl, Corinna; Hub, Elin; Eller, Philipp; Rosenkranz, Alexander; Eller, Kathrin; Rot, Antal
Abstract: BACKGROUND AND AIMS: The overwhelming majority of individuals of West African ancestry carry an 'erythroid silent' FyB(ES) SNP in the promoter region of ACKR 1 that causes a selective loss of ACKR1 in erythroid cells but does not affect its expression in endothelial cells. The FyB(ES) polymorphism is of a special interest for understanding human kidney disease as individuals of West African ancestry have higher incidence of chronic kidney disease. Moreover, multiple chemokine ligands of ACKR1 are known to contribute to the inflammatory pathology in experimental nephrotoxic serum nephritis (NTS), a murine model of immune complex glomerulonephritis. METHOD: We developed two humanized transgenic mouse strains that are genetically deficient for mouse ACKR1 but instead carry either West African FyB(ES) or Caucasian FyB human polymorphic ACKR1 variants. These strains as well as ACKR1-deficient and WT mice were subjected to NTS. The parameters of immunopathogenesis and kidney disease were evaluated after 14 days after the induction of NTS. RESULTS: Albuminuria, PAS and tubular injury scores were significantly increased in FyB(ES)tg and ACKR1-deficient mice as compared with their respective control strains. While monocytes were unchanged in peripheral blood, we found significantly increased numbers of macrophages and neutrophils infiltrating the kidneys of FyB(ES)tg and ACKR1-deficient mice. Interestingly, T cell numbers in the draining lymph nodes were comparable between FyB(ES)tg and ACKR1-deficient mice and their respective controls. CONCLUSION: We found that NTS was more severe in ACKR1-deficient and FyB(ES) mice as compared with their respective controls. Our results show that ACKR1 expression in the erythroid compartment has a significant impact on the development of kidney disease. These findings have important implications for the pathomechanisms of glomerulonephritis in individuals of West African ancestry who lack ACKR1 selectively in the erythroid lineage.